Somatic embryogenesis in Larix: the state of art and perspectives - V. N. Shmakov; Yu. M. Konstantinov (Вавиловский журнал генетики и селекции)
Clonal propagation of conifers using somatic embryogenesis is essential for the selection of tree species, and for the implementation of afforestation and reforestation. In combination with cryopreservation, somatic embryogenesis creates the basis for the development of economically valuable lines of clones and elite genotypes. The industrial use of such genetically verified clone lines in forestry can significantly increase forest productivity compared to any conventional methods for improving tree crops that are available. Larch is considered as one of the main conifer candidates for large-scale reforestation, not only due to the vastness of its habitat, but also due to the unique quality of its wood, rapid growth and high ecological plasticity. However, the vast majority of larch species are characterized by uneven yields and extremely low seed quality. In this regard, obtaining planting material for reforestation from larch seeds on seed plantations is not advisable, but can be successfully implemented in afforestation programs using somatic embryogenesis technologies. Research on the somatic embryogenesis of larch has been conducted for over 30 years, which allowed considerable experience in this field to be accumulated. To date, the conditions for the initiation and maintenance of embryogenic cultures, as well as for the formation and development of somatic embryos have been determined. Significant progress has been made in the study of both the factors affecting these processes and the molecular mechanisms that underlie the various stages of embryogenesis. Nevertheless, despite the successes achieved, knowledge available today on the somatic embryogenesis of representatives of the genus Larix is still not enough to develop technologies for producing valuable plant-breeding material in vitro. This review analyzes the current state of research on the problem of somatic embryogenesis of representatives of the genus Larix. Particular attention is paid to the choice of explants for somatic embryogenesis, the composition of the media for cultivation, the dependence of the potential of somatic embryogenesis on the duration of cultivation, and the genetic control of somatic embryogenesis.